Human dietary exposure to chemicals in sub-Saharan Africa: safety assessment through a total diet study. Issue 7 (July 2020) - Ingenbleek, Luc; Verger, Philippe; Gimou, Marie-Madeleine; Adegboye, Abimbola; Adebayo, Samson B; Hossou, Sètondji Epiphane; Koné, Abdoulaye Zié; Jazet, Eric; Dzossa, Anaclet D; Ogungbangbe, Julius; Dansou, Sylvestre; Diallo, Zima J; et al.
Summary: Background: Human dietary exposure to chemicals can result in a wide range of adverse health effects. Some substances might cause non-communicable diseases, including cancer and coronary heart diseases, and could be nephrotoxic. Food is the main human exposure route for many chemicals. We aimed to assess human dietary exposure to a wide range of food chemicals. Methods: We did a total diet study in Benin, Cameroon, Mali, and Nigeria. We assessed 4020 representative samples of foods, prepared as consumed, which covered more than 90% of the diet of 7291 households from eight study centres. By combining representative dietary surveys of countries with findings for concentrations of 872 chemicals in foods, we characterised human dietary exposure. Findings: Exposure to lead could result in increases in adult blood pressure up to 2·0 mm Hg, whereas children might lose 8·8–13·3 IQ points (95th percentile in Kano, Nigeria). Morbidity factors caused by coexposure to aflatoxin B1 and hepatitis B virus, and sterigmatocystin and fumonisins, suggest several thousands of additional liver cancer cases per year, and a substantial contribution to the burden of chronic malnutrition in childhood. Exposure to 13 polycyclic aromatic hydrocarbons from consumption of smoked fish and edible oils exceeded levels associated with possible carcinogenicity and genotoxicity health concerns in all study centres. Exposure to aluminium, ochratoxin A, and citrinin indicated a public health concern about nephropathies. From 470 pesticides tested across the four countries, only high concentrations of chlorpyrifos in smoked fish (unauthorised practice identified in Mali) could pose a human health risk. Interpretation: Risks characterised by this total diet study underscore specific priorities in terms of food safety management in sub-Saharan Africa. Similar investigations specifically targeting children are crucially needed. Funding: Standards and Trade Development Facility.